Mauritius: Recent developments in public agricultural research - Rahija, Michael; Ramkissoon, Jairaj; Stads, Gert-Jan (International Food Policy Research Institute, 2010)
After a period of steady increases throughout the 1990s, public agricultural research and development (R&D) expenditures in Mauritius began to decline from 2002. In 2008, the country invested 336 million Mauritian rupees or 23 million PPP dollars on agricultural R&D, compared with 456 million rupees or 31 million PPP dollars in 2002 (in 2005 prices), representing a decrease of about 25 percent. Note that, unless otherwise stated, all dollar values in this note are based on PPP exchange rates. PPPs reflect the purchasing power of currencies more effectively than do standard exchange rates because they compare prices of a broader range of local-as opposed to internationally traded-goods and services. Despite the gradual declines in agricultural R&D investments, Mauritius expanded its agricultural research capacity somewhat since the turn of the millennium to 178 full-time equivalent (FTE) researchers in 2008.